Pendidikan Profetik Dalam Konteks Global: Tantangan dan Peluang - Wahyu Ningsih; Rohani Rohani; Sifa Safitri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This journal explores the impact and dynamics of prophetic education in a global context, highlighting the challenges and opportunities faced. Through a literature analysis approach, this research investigates how Islamic prophetic values can be significantly integrated into diverse global education systems. Identified challenges include cultural differences, varying understandings of Islam, and rapid social change. On the other hand, opportunities arise in the form of cross-cultural collaboration, global knowledge exchange, and the development of innovative educational strategies. By delving deeper, this journal provides insight into how prophetic education can be an important instrument for building better understanding, harmony and tolerance in an increasingly complex global educational environment.